Women and religious traditions (Oxford Univ. Press, 2004)
"Women and Religious Traditions provides an introduction to the issues facing women in a wide range of religious traditions. Hindu, Jewish, Buddhist, Chinese, Indigenous, Christian, Muslim, and New Age. Each of the eight essays offers an introduction to the main elements of the religion and then explores shifting roles of women within that faith. The essays are organized around five main themes." "Each essay follows the same basic structure, allowing the reader to make useful comparisons across these widely divergent religious traditions. This book will be a resource for students beginning their inquiry into religious studies, as well as for more advanced students looking to deepen their understanding of the relationship between feminist inquiry and religious studies."--BOOK JACKET.